A Preliminary Study Of Academicians’ Perception Towards Women PN Boards In Malaysian Public Listed Companies - Farhana Hasbolah; Mohamad Hafiz Rosli; Siti Aisyah Omar (Universitas Serang Raya, 2021)
Gender diversity in the corporate board is still an issue for certain countries including Malaysia. The Malaysian Code of Corporate Governance (MCCG) 2017 anticipates 30% of women to be on the corporate board. However, recently the number of women on board reported is still lower. This study aims to examine the perception of academician towards women on board (WOB). The survey questionnaires were sent among academicians. The result indicates that the academicians believe that the appointment of women on boards will improve and enhance the companies’ performance. There are equal opportunities for men and women to be in management positions. The finding of this study will assist the policymakers and companies especially in formulating women policy to support the national agenda.